(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The present study examines the evolution of the normative framework of end of life decisions under spanish law in order to understand the recent legalisation of assisted death by the organic law 3/2021 on euthanasia. it also analyses how assisted death has been regulated, with particular attention to its substantive and procedural requirements, and highlights some issues whose implementation is probably going to be problematic.